Comparison of Vortex Induced Velocity Kinematics around Underwater Horizontal Cylinder with Vertical End Plate. Issue 1 (February 2021) - Kuila, A; Mukherjee, B; Das, S
Abstract: Electrical energy is harnessed from various natural sources to protect the environment and ecology which is termed as green energy sources. When vortex is induced on a cylinder, it starts vibrating according to the formation of vortex. The vibration is so strong that it can destroy any structure wherever alternating vortex is induced. Currently Vortex Induced Vibration is used to harness electrical energy from ocean, river and shallow water channel. In this paper, experimental investigations were conducted in flume to analyse the behaviour of underwater flow structures around a 5 cm horizontal cylinder placed transversely to the flow at 60% and 70% depths from water surface and simultaneously a 5 cm wide vertical end plate set at 8 cm downstream from cylinder. Fluctuating 3D velocity components around such plate cylinder combination were measured. From subsequent plotted contours, changing flow patterns in presence of vertical plate are analysed. Hydrodynamic flow features are shown by plotting absolute velocity fields and velocity vectors. It visualizes that streamlines separate first and then passes over the periphery of horizontal cylinder. The contour of turbulence kinetic energy confirms the presence of strong vortex in between horizontal cylinder and vertical plate. The horseshoe vortex at the upstream of cylinder becomes stronger due to the presence of vertical plate. The results from these two experiments are compared with the results observed in previous researches. With the increase in cylinder depth from water surface, the horseshoe vortices strength becomes stronger.